2013
DOI: 10.1371/journal.pone.0065067
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Inactivation of p53 in Mouse Ovarian Surface Epithelium Does Not Alter MIS Driven Smad2-Dominant Negative Epithelium-Lined Inclusion Cysts or Teratomas

Abstract: Epithelial ovarian cancer is the most lethal gynecological malignancy among US women. The etiology of this disease, although poorly understood, may involve the ovarian surface epithelium or the epithelium of the fallopian tube fimbriae as the progenitor cell. Disruptions in the transforming growth factor beta (TGFβ) pathway and p53 are frequently found in chemotherapy-resistant serous ovarian tumors. Transgenic mice expressing a dominant negative form of Smad2 (Smad2DN), a downstream transcription factor of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…The finding that TGFβ1 increased phospho-Smad2/3 levels, but did not increase migration, suggested that the increased migration was Smad independent. Confirming this, a previously validated dominant negative Smad2 (Smad2DN) construct [37,38] did not abrogate the migratory effect of activin A (Figure 2A). The Smad2DN construct blocked phosphorylation of Smad2/3 (Figure 2B).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The finding that TGFβ1 increased phospho-Smad2/3 levels, but did not increase migration, suggested that the increased migration was Smad independent. Confirming this, a previously validated dominant negative Smad2 (Smad2DN) construct [37,38] did not abrogate the migratory effect of activin A (Figure 2A). The Smad2DN construct blocked phosphorylation of Smad2/3 (Figure 2B).…”
Section: Resultssupporting
confidence: 70%
“…The Smad2-dominant negative (Smad2DN) construct was a gift from Teresa Woodruff at Northwestern University and has been previously validated [37,38]. Cells were transfected with 500 ng/ml Smad2DN plasmid or empty vector (pcDNA3) with ViaFect (E4981, Promega, Madison, WI) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 million cells suspended in PBS were injected into the peritoneal cavity via IP injection. All attenuated adenovirus was used at a concentration of 10 10 plaque forming units (pfu)/ml (Iowa Gene Transfer Vector Core, Iowa City, IA) and in vivo administration was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…It has been found that activin, via Smad2/3 receptors, activates PI3 Akt pathway, existing in epithelial ovarian carcinomas, and affects the overexpression of antiapoptotic genes [28], [29]. Complicated interactions among inhibin, activin, estrogens and NF-κB signal pathway have been proven [30].…”
Section: Discussionmentioning
confidence: 99%